Gestión de inventarios y la merma de productos perecederos en Hipermercados Tottus Oriente S.A.C. Precio Uno Iquitos 2023 - López Espinoza, Adrian (2025)
Hypermarkets face difficulties in managing their inventories and minimizing losses of perishable products. This is largely due to the lack of an efficient system to control and monitor stored products. In addition, inadequate demand planning and product rotation exacerbate the problem. This research aimed to determine the relationship between inventory management and the shrinkage of perishable products in Tottus Oriente S.A.C. Hipermercados Precio Uno in Iquitos during 2023. The study was applied, descriptive-correlational, non experimental design, with a quantitative approach and cross-sectional, a sample of 25 employees was selected, which included managers, supervisors and employees of the company Precio Uno in Iquitos, the sampling was of the census type. The procedure used consisted of applying a questionnaire, using the Likert scale to evaluate the inventory management and shrinkage variables. To ensure the accuracy and consistency of the study, the reliability of the instrument used to collect data was evaluated, using Cronbach's Alpha as a measure of reliability, and according to the established range table, the instrument obtained a coefficient of 0.838, which indicates a good level of reliability for use in research. The analysis of the collected data, carried out using the statistical programs Excel and SPSS version 26, revealed crucial information about the perception of the variables studied. Regarding V1: Inventory Management, 32% of the survey participants rated it at a medium level, while the remaining 68% considered it to be at a high level. On the other hand, V2: Shrinkage was perceived as medium level by 16% of the sample, and 84% gave it a high-level rating. The findings obtained in the inferential statistics determined a Pearson's correlation coefficient r of -0.251 with a 2 tailed sig. of 0.226 > 0.005, which indicates that there is no significant relationship between both study variables. As defined in the information obtained through descriptive and inferential statistics, it is concluded that both V1 and V2 present moderately high levels of management, which demonstrates certain deficiencies in the handling of perishable products, caused by different factors. In the results of the inferential statistics, it was determined with Pearson's correlation coefficient r that both variables are not related to each other, and that Inventory Management and Shrinkage are related to other variables.